Preliminary study on benthic macroinvertebrates distribution and assemblages at Lata Meraung Waterfall, Pahang, Malaysia - Sharifah Aisyah Syed Omar; Aweng Eh Rak; Razak Wahab; Ahmad Abas Kutty (2015)
This study aimed to identify the distribution and assemblages of benthic macroinvertebrates at Lata Meraung Waterfall, Pahang, Malaysia. Benthic macroinvertebrates were collected between 11-12 February 2014 from three stations located at upstream, midstream and downstream of the river. Benthic macroinvertebrates were collected by using Surber net with 500 micron mesh size combined with a rectangular quadrate with the size of 30 cm x 30 cm. The ecological indices (richness, diversity, dominant, and evenness) and benthic biotic index (Ephemeroptera, Plecoptera and Trichoptera or EPT) were calculated. Result shows that, the study area was dominated by insects where a total of 1,287 individuals from 27 taxa of insects were collected. The most abundant taxon was Hydropsychidae (Trichoptera) which contributed about 20% of total individuals. On the other hand, all stations recorded the present of sensitive organisms namely Ephemeroptera, Plecoptera and Trichoptera (EPT) but Trichoptera (Hydropsichidae) was the most abundant with 264 individuals. However, Ephemeroptera was the most diverse with seven families as compared to Plecoptera and Trichoptera. The assemblages of benthic macroinvertebrates were abundance at the downstream as compared to upstream. This was due to the composition of substrates such as sand, pebble, and cobble which are lesser at the upstream river.